Peasant economy and control spaces from the study of the fairs of a region - CCAIJO, Equipo (1984)
We have been interested in the study of this topic because, as part of an adult education team, the need to better understand the broad and complex peasant world, its production process, its daily life and the mechanisms to face its subsistence, is a task that is imposed on us every day. And, within it, the moment of exchange was a fundamental aspect for us to contribute some reflections about the peasant economy.